Genetic diversity of soybean cultivars belonging to different ripeness groups with regard to performance and quality - A. I. Abugaliyeva; S. V. Didorenko (Вавиловский журнал генетики и селекции)
Twenty six varieties of Kazakstani and 42 soybean breeding varieties from Russia, Ukraine, France, and Serbia have been studied. Depending on the length of the vegetation period from within 90–135 days, these varieties were divided into five ripeness groups. None of the Kazakstani varieties has been assigned to early season ripening group 00. Varietes in the mid-late and middle season ripening group, which are the most adapted to the cultivation conditions in the southeastern area of Kazahstan, showed the highest yield. Kazakstani varieties have been found superior to the others in average yield by 2.3 q/ha in mid-early group 0, by 3.6 q/ha in mid-late group II, and by 7.9 q/ha in late group III. The highest range of variation and the maximum level of protein collection was characteristic of the middleand of medium group. The amounts of protein and fat in the Kazakhstani and other varieties within the groups was found to be almost identical; at the same time, there was a notable positive correlation between precocity and high protein content. As a result, early-ripening soybean genotypes (groups 000 and 00) with promise for cultivation in the northern areas of the Republic of Kazakhstan have been identified and put together as a whole. The most productive Kazakstani variety was Zhansaya (included in the register of the Republic of Kazakhstan in 2012), which yielded 38.3–45.8 q/ha over the study period. High-protein variety Zara, with a protein content of 37.7 %–43.3 %, has been in variety testing in the Republic of Kazakhstan since 2011.